Analisis permintaan telur ayam ras di Kabupaten Manokwari - Suawa, Elfira; Sitanggang, Fransiska Rianti Verawati; Widayati, Trisiwi W.; Manik, Hotlan (Cassowary, 2025)
Demand analysis is essential for providing information that serves as a reference in formulating government policies for managing livestock products. This study aimed to analyze the factors influencing the demand for chicken eggs in Manokwari Regency. Secondary data covering the period 2013–2022 were obtained from the Manokwari Class II Agricultural Quarantine Station and several agencies in West Papua Province, including the Central Bureau of Statistics (BPS), the Department of Industry and Trade, the Department of Fisheries and Marine Affairs, and the Department of Animal Husbandry and Animal Health. The data were analyzed using linear regression with the Ordinary Least Squares (OLS) method. The results showed that the demand for chicken eggs in Manokwari Regency was influenced by the price of chicken eggs, the price of free-range chicken eggs, the price of duck eggs, the price of beef, the price of rice, the price of tempeh, and the population size.